Amino acids in animal feed: significance and determination techniques. Issue 1 (October 2021) - Sefer, M; Petronijevic, R B; Trbovic, D; Ciric, J; Baltic, T; Parunovic, N; Djordjevic, V
Abstract: Amino acids are fundamental for animal nutrition. Their presence is necessary to maintain the normal structure and function of the intestine, and they are key in regulating metabolic pathways for improving health, survival, growth, development, lactation, and reproduction. The animal feed industry invests great resources and efforts to obtain optimal formulations in which the composition of amino acids plays a key role. In support of these aspirations in recent decades, much attention has been paid to the development and improvement of analytical techniques for the reliable, rapid and accurate determination of amino acid content in animal feed. This paper outlines different methodologies for the analysis of amino acid content in animal feed. Various methods, based on different analytical techniques, are presented for determination of amino acids in feed for nutritional and regulatory purposes.